DENALI FAULT SLIP RATES AND HOLOCENE-LATE PLEISTOCENE KINEMATICS OF CENTRAL ALASKA - Matmon A.; Schwartz D.P.; Lienkaemper J.J.; Stenner H.D.; Dawson T.E.; Haeussler P.J.; Finkel R. (My University, 2006)
The Denali fault is the principal intracontinental strike-slip fault accommodating deformation of interior Alaska associated with the Yakutat plate convergence. We obtained the first quantitative late Pleistocene-Holocene slip rates on the Denali fault system from dating offset geomorphic features. Analysis of cosmogenic 10Be concentrations in boulders (n = 27) and sediment (n = 13) collected at seven sites, offset 25-170 m by the Denali and Totschunda faults, gives average ages that range from 2.4 ± 0.3 ka to 17.0 ± 1.8 ka. These offsets and ages yield late Pleistocene-Holocene average slip rates of 9.4 ± 1.6, 12.1 ± 1.7, and 8.4 ± 2.2 mm/yr-1 along the western, central, and eastern Denali fault, respectively, and 6.0 ± 1.2 mm/yr-1 along the Totschunda fault. Our results suggest a westward decrease in the mean Pleistocene-Holocene slip rate. This westward decrease likely results from partitioning of slip from the Denali fault system to thrust faults to the north and west. © 2006 Geological Society of America.
Keywords: COSMOGENIC ISOTOPES; DENALI FAULT; OFFSET MORAINES; SLIP RATES; Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен